Study on slope stability under excavation and water storage based on physical model tests - Chengheng Hou; Chengheng Hou (Frontiers in Earth Science, 2023)
Understanding the characteristics and mechanism of slope deformation caused by slope excavation and water storage is very important in the stability analysis of slope engineering. Therefore, based on similarity theory, a physical model test of excavation and water storage was established, and the deformation characteristics of the slope (three-stage excavation and five-stage water storage) were studied by using the monitoring technology of multiple measuring devices. The variation characteristics of the displacement, stress and pore water pressure in the slope were revealed. The results show that the contents of cement and yellow sand can regulate the physical, mechanical and hydrological properties and that gypsum and hydraulic oil have an effect on the permeability. Excavation leads to deformation of the rock mass in the middle and lower slope to the outside of the slope. This is attributed to the stress release, and local stress concentration occurs at the foot of the slope after redistribution. Moreover, the rock mass located in the fault zone shows nonglobal movement because the hanging wall rock mass will produce relative dislocation along the fault zone under self-gravity. Under water storage, the slope body is affected by the hydrostatic pressure, and transient compaction deformation occurs first. As water permeates into the slope body, the water weakens the rock mass, resulting in the gradual deformation of the rock mass near the slope surface to the outside of the slope. The above model test results can provide a valuable reference for slopes stability analysis in construction and subsequent operation.